Earnings attainment in the three main cities of Southeastern Brazil: Social networks and communities of worship - Silvio Segundo Salej Higgins; Jorge Alexandre Barbosa Neves; Luciano Mattar (Journal for Labour Market Research, 2025)
Following the field of insertion into the labor market, we tested the classic hypothesis of the strength of weak ties in the three largest cities in the Southeast Region of Brazil, with a focus on communities of religious worship. A survey was carried out in 2021 with 900 questionnaires divided equally among the three cities, weighted considering the size of the population and the distribution of religious affiliation. We investigated: (1) whether the strength of ties leverages the labor insertion of adults; (2) whether religious cult communities operate as mechanisms for the circulation of opportunities in the labor market. The data were analyzed with Heckman's two-stage correction models to mitigate possible censoring biases. Controlling by seniority in the position and participation of three sampled cities in gross national product, inter alia, the results show that strong ties, as predicted by the strength of ties theory, are associated with lower earnings. At the same time, obtaining a paid job through another cult member is negatively associated with earnings. However, when testing our main hypothesis, we found that in the three largest cities in the Southeast Region of Brazil the religious embeddedness, composed of strong ties, high worship attendance and religious motivations coming from maternal ties, operate plausibly in labor market as favorable screen mechanism associated with higher earnings.
Keywords: J69; 330; Communities of worship; Earnings attainment; Religious~embeddedness; Strength of ties